2003
DOI: 10.1071/bt03016
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow between introduced and native Eucalyptus species: exotic hybrids are establishing in the wild

Abstract: Abstract. F 1 hybrids between exotic Eucalyptus nitens plantations and native E. ovata have previously been reported among seedlings grown from open-pollinated seed collected from E. ovata, on the island of Tasmania. Such exotic hybrid seedlings have now been found in the wild adjacent to plantations at three locations. The proportion of exotic hybrids in open-pollinated seed collected from nearby mature E. ovata was 5.5%. This level compares with only 0.4% for natural hybrids between native species at these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…Because of the very similar juvenile morphology of E. globulus and E. nitens, this could result in situations where the parentage of hybrids detected with E. ovata would be ambiguous. Exotic hybrids between E. ovata and both plantation species are well known [31,79] and do show similar morphology. The three-way simulation (E. globulus, E. nitens, and E. ovata) here showed the utility of the microsatellite based approach in overcoming ambiguity in this situation, and it could be an important management tool for distinguishing between exotic and natural hybridisation where E. nitens grows within the native range of E. globulus.…”
Section: Performance Of the Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the very similar juvenile morphology of E. globulus and E. nitens, this could result in situations where the parentage of hybrids detected with E. ovata would be ambiguous. Exotic hybrids between E. ovata and both plantation species are well known [31,79] and do show similar morphology. The three-way simulation (E. globulus, E. nitens, and E. ovata) here showed the utility of the microsatellite based approach in overcoming ambiguity in this situation, and it could be an important management tool for distinguishing between exotic and natural hybridisation where E. nitens grows within the native range of E. globulus.…”
Section: Performance Of the Approachmentioning
confidence: 99%
“…An assessment of the species growing where the hybrid was collected would probably narrow down the number of potential parents. Also most exotic plantation hybrids identified in the field are found among pure seedlings of the native species [31,83], likely enabling the identification of a single putative maternal species. In an operational context where a putative exotic hybrid has been identified in the field, an effective approach may be to run a full six-way analysis to rule out other species contributing pollen, which can travel long distances [84], then reduce the number of species to those found in the vicinity of the putative hybrid.…”
Section: Performance Of the Approachmentioning
confidence: 99%
“…These hybrid seedlings originated from open pollinated seed from an E. nitens seed orchard that was surrounded by native forest containing E. ovata and E. viminalis. Subsequent research revealed that exotic E. nitens hybrids were also occuring in open pollinated seed collected from the adjacent E. ovata trees (hybridisation rate ranged from 0.04 to 16% per tree - Barbour et al 2002), demonstrating a potential avenue for exotic gene flow. Furthermore, E. ovata × nitens hybrid seedlings were found soon after, growing in disturbed areas near plantations .…”
Section: The Case Of Eucalyptus Nitens In Tasmaniamentioning
confidence: 99%
“…Hybridisation was highest on the edges of patches and declined very rapidly with distance. the species means that detection of exotic hybrids in the wild has usually been restricted to early life cycle, first generation hybrids (F 1 s between exotic plantation species and a native eucalypt - Figure 1) (Barbour et al 2002;Barbour et al 2003;Barbour et al 2008b;Larcombe et al 2014), although progression to the second generation of hybridisation (F 2 and backcrossing) has been reported in Corymbia (Shepherd & Lee 2016).…”
mentioning
confidence: 99%
“…Because trees are perennial plants with a long rotation time and remain in the same place for a considerable period, long-term evaluation of the impact of GM trees on the surrounding environment is required (Owusu 1999). Furthermore, for many trees, little is known of their physiology and genetics (Owusu 1999;Valenzuela et al 2006), and in many cases, tree species generate interspecific hybrids (e.g., Quercus, Populus and Eucalyptus) (Barbour et al 2003;Ubukata 2003;Brooker 2000). Their pollen and seed dispersal distances are not well-known, and unforeseen acceptors of GM pollen undoubtedly exist around the plantation area.…”
Section: Treesmentioning
confidence: 99%